Lush - Friend, Natasha (New York Children's Press, 2006)
Unable to cope with her father's alcoholism, thirteen-year-old Sam corresponds with an older student, sharing her family problems and asking for advice
Includes bibliographical references (p. 181-184)
Hurg
5 8
Keywords: Alcoholism -- Fiction; Family problems; Fathers -- Fiction